(untitled) (Bangladesh Journal of Neurosurgery, 2019)
We report a case of a 20 years old female patient, who presented with the complaints of progressive quadriparesis which eventually led to quadriplegia. Her weakness started from the right side of the body and then to the left. Her MRI of the neck revealed an extradural lesion extending from the C2 up to C6 vertebral level. It had compressed the dural tube to the left. The lesion continued to the neck through the inervertebral foramen at C6. Her CT angiogram of the neck vessels showed an AVM arising from the right SCA and entering the Spinal canal at C6 level and draining into the right IJV at C2 level. She underwent surgery and the AVF was ligated at the origin. The AVM had collapsed. After 15 days following surgery, she had significant improvement of symptoms. After one and half months she could walk with support. Bang. J Neurosurgery 2019; 9(1): 69-74